Les Années d’Annie Ernaux en traduction polonaise : des contextes aux paratextes. Analyse des notes du traducteur - Warmuzińska-Rogóż, Joanna (2023)
The article concerns the Polish translation of Les Années by Annie Ernaux, published by Czarne in 2022. Translators, Krzysztof Jarosz and Magdalena Budzińska, who is also the editor of the volume, filled out a questionnaire proposed by the author of the article that aims to find out the strategy regarding cultural elements, but also the presence of footnotes. The article contains the analysis of various types of footnotes and various strategies resulting from translation dominant selected by the translators, visible in the Polish translation.
Keywords: Annie Ernaux